Sky polarization pattern under multi-layer environment of atmosphere and sea fog - Fu, Qiang; Liu, Yang; Liu, Nan; Si, Linlin; Zhang, Su; Zhan, Juntong; Li, Yingchao (Frontiers in Physics, 2022)
The vertical polarization distribution pattern of sea fog multilayer media and skylight in the atmosphere is explored. To change the complicated maritime environment, the simplified double layer structure of the atmosphere and sea fog is employed, and the scattering coefficients of the uniform atmosphere and sea fog medium are derived using the Rayleigh and Mie scattering methods, respectively. Using the adding-doubling method (RT3) based on the vector radiation transmission equation, the transmission of radiation between the two layers of the medium is calculated to obtain the polarization distribution conditions of skylight, and the variation tendency of the polarization characteristics observed from the ground is studied for the downwelling radiation of sea fog on the meridian of the sun. An indoor sea fog setting was employed to perform the polarization transmission test, and the relationship between humidity, light intensity transmittance, and polarization degree was explored. The data suggest that the sun's position gives the lowest degree of polarization, and that the maximum value is obtained when the angle between the solar altitude angle and the observed altitude angle is 90°. Short wavelength lasers have a higher influence on optical transmittance than long wavelength lasers do when humidity levels increase. The circular polarization effect of long wavelength laser is better in damp surroundings.